Detection of macular and peripheral ocular microvascular changes after carotid artery revascularization using widefield SS-OCTA - Ting Luo; Lu Wang; Li Zhang (Frontiers in Medicine)
PurposeThis study aims to investigate microvascular changes in the macular and peripheral regions, as well as alterations in the foveal avascular zone (FAZ) of the ipsilateral eye using widefield swept-source optical coherence tomography angiography (SS-OCTA) in patients with severe carotid artery stenosis (SCAS) after carotid artery revascularization (CAR).DesignThis study employed a prospective study design.MethodsSCAS patients were examined using widefield SS-OCTA, which covered an area of 16 × 16 mm centered on the fovea. These examinations were conducted both before and after CAR to assess changes in retinal and choroidal blood flow in the macular and peripheral regions, as well as alterations in the characteristics of the FAZ.ResultsA total of 56 patients and their corresponding 56 ipsilateral eyes were included in this study. In the macular area, a significant increase in the vessel density of the retinal superficial vascular complex (VDRSVC) was found, while a significant decrease was noted in the vessel density of the retinal deep vascular complex (VDRDVC) after CAR. Additionally, both the area and circumference of the FAZ decreased significantly after CAR. In the peripheral regions, significant increases were detected in both VDRSVC and the three-dimensional choroidal vascularity index (3D-CVI) post-CAR.ConclusionThe findings of this study demonstrated that CAR can improve perfusion in both the macular and peripheral fundus and lead to a decreased area and circumference of the FAZ in the ipsilateral eye. The observed decrease in the VDRDVC after CAR may be attributed to microvascular embolization and ischemia within the deep capillary plexus (DCP).